Effect of Low Compression on the Growth Plate. An Experimental Study in Sheep - Asimus, E.; Collard, P.; Sales de Gauzy, J.; Mathon, D.; Darmana, R.; Cahuzac, J.-Ph.; Autefage, A. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
This study was carried out to investigate the effect of compression on the growth plate. An external fixation device was applied across the distal radial physis in 24 eight-week-old lambs. Compression was applied continuously for seven weeks. A shamoperation was performed on the contralateral side. The animals were divided into two groups according to the rate of compression. In group #1, the mean pressure exerted by the compression device ranged from 0.03 ± 0.01 kg/cm2 to 0.05 ± 0.01 kg/cm2. In group #2, the mean pressure ranged from 0.08 ± 0.01 kg/cm2 to 0.16 ± 0.01 kg/cm2. The results obtained show that this pressure did not modify the longitudinal growth of the bone. A statistical difference was not noted between the operated side and the control side in any of the groups. We conclude that mild physeal compression (less than 0.16 kg/cm2) in the immature sheep would neither retard nor accelerate the growth of the distal radial epiphyseal plate.An external fixation device was applied to the distal radial growth plate in immature sheep. Compression was performed continuously for seven weeks. The authors conclude that mild physeal compression (between 0.03 and 0.16 kg/cm2) neither diminished nor increased the growth.
Keywords: Growth plate; biomechanics; growth regulation; sheep